The impact of environmental emissions and aggregate economic activity on industry : theoretical and empirical perspectives - Pal, Mihir Kumar, 1965- (Emerald Publishing Limited, 2023)
As economic growth continues to rise, so does economic degradation. Though certain rules and regulations do exist, pollution is fast becoming an unpaid factor of production, unlike the remunerations of labour and capital inputs. In this context, the environment is thus used as a factor of production which is not fully compensated. However, its use in the production process can be accurately captured by introducing emissions as an input in an aggregate production function, as Mihir Kumar Pal and other leading experts demonstrate. In a reverse approach, they examine the effect of emissions on industrial growth as opposed to that of growth on emissions, enhancing an awareness of this pivotal trade-off where the intersection between economy and environment currently needs it most. Offering both theoretical and empirical perspectives, The Impact of Environmental Emissions and Aggregate Economic Activity on Industry: Theoretical and Empirical Perspectives is an insightful and original contribution to the sustainable development and economics canon.
Keywords: Industries -- Environmental aspects.; Air -- Pollution.; Production (Economic theory) -- Environmental aspects.; Business & Economics -- Development -- Economic Development.; Economic growth.; elektronické knihy; electronic books